Derivational Suffixes in The La La Land Movie - Ida Ayu Kartika Lestari; I Wayan Arka; I Nyoman Udayana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study with the title Derivational Suffixes in La La Land Movie. This study aims to identifying the derivational suffixes and the functions of derivational suffixes in La La Land movie. Descriptive qualitative methods are used in this study to analyze the derivational suffixes and the functions of derivational suffixes in La La Land movie. The data was taken from the movie script of the La La Land movie. The data were collected using note taking method through, reading carefully, highlighting, and classifying the types and the function. The collected data was analyzed using qualitative method and explained descriptively. Tree diagram also used in this study in order to explain the data. This study applied the theory proposed by (Plag, 2002) in order to identify the derivational suffixes and also applied the theory proposed by (Bauer, 1983) in order to identity the functions of derivational suffixes. The results of this study show there were four types of derivational suffixes found. Those data can be divided into nominal suffixes, adjectival suffixes, adverbial suffixes, and verbal suffixes. Meanwhile for the functions, there are 2 kinds functions found in the data such as class-maintaining and class-changing.